Examining the Effect of Parents on Children's Career Choices in the Context of Class Positions - Akcelik, Emine; Ustun, Alkan; Akçelik, Emine; Üstün, Alkan (Sosyoekonomi Soc, 2024)
This article delves into the social mobility strategies employed by parents and their descendants from diverse social classes in structuring educational pathways and vocational choices across successive generations. The study relies on qualitative data from in-depth interviews conducted in Ankara with 24 parents and 18 offspring. Data analysis reveals that the strategies parents and their offspring embrace are intricately shaped by their social class positions and the cultural, social, and economic capital available to the latter. Labourer families grappling with cultural capital limitations exhibit constrained guidance to their offspring. In contrast, self-employed professional families actively deploy their comprehensive cultural capital to perpetuate privileged class positions across generations. Business owners or commercial entrepreneurs, characterised by a distinctive outlook, view education as a pathway to attain heightened social status rather than as a means of upward mobility. To address the inequalities uncovered in this research, establishing counselling centres for families to guide how to mentor their children and for the children themselves to facilitate the discovery of their abilities and interests could offer a solution toward mitigating these inequalities.
Examining the Effect of Parents on Children’s Career Choices in the Context of Class Positions
Keywords: Social Class; Social Mobility; Status; Stratification